2019
DOI: 10.1096/fj.201900578rr
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional memory inherited from donor cells is a developmental defect of bovine cloned embryos

Abstract: Studies on the effects of transcriptional memory on clone reprogramming in mammals are limited. In the present study, we observed higher levels of active histone H3 lysine 4 trimethylation (H3K4me3 and 5‐hydroxymethylcytosine) and repressive (5‐methylcytosine) epigenetic modifications in bovine early cloned embryos than in in vitro fertilized embryos. We hypothesized that aberrant epigenetic modification may result in transcriptional disorders in bovine somatic cell nuclear transfer (SCNT) embryos. RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Many different determinants have been identified to be related to SCNT efficiency. They encompass (1) cytological and molecular quality of nuclear recipient oocytes characterized by meiotic, cytoplasmic, and epigenomic maturity parameters (Samiec & Skrzyszowska, 2012; Wang et al, 2018; Gupta et al, 2019); (2) the origin and phenotype of nuclear donor cells (Madheshiya et al, 2015; Em et al, 2016); (3) the capability of donor cell nuclear genome to be epigenetically reprogrammed in a cytoplasm of nuclear-transferred oocytes and descendant blastomeres of corresponding cloned embryos (Opiela et al, 2017; Monika & Selokar, 2018; Samiec & Skrzyszowska, 2018 a , 2018 b ; Zhou et al, 2020); (4) molecular and epigenetic communication between nuclear and mitochondrial genomes in nuclear-transferred oocytes and resultant cloned embryos (Hiendleder et al, 2003; Samiec, 2005 a , 2005 b ; Srirattana et al, 2011); (5) the strategies applied to artificially activate embryo-specific developmental programme of nuclear-transferred oocytes (Saikhun et al, 2004; Samiec & Skrzyszowska, 2010, 2014; George et al, 2011); and (6) the frequency of occurrence of apoptosis-dependent events in the in vitro -cultured nuclear donor cells and SCNT-derived embryos (Cui et al, 2011; Samiec et al, 2013; Agrawal et al, 2018; Mehta et al, 2019; Samiec et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many different determinants have been identified to be related to SCNT efficiency. They encompass (1) cytological and molecular quality of nuclear recipient oocytes characterized by meiotic, cytoplasmic, and epigenomic maturity parameters (Samiec & Skrzyszowska, 2012; Wang et al, 2018; Gupta et al, 2019); (2) the origin and phenotype of nuclear donor cells (Madheshiya et al, 2015; Em et al, 2016); (3) the capability of donor cell nuclear genome to be epigenetically reprogrammed in a cytoplasm of nuclear-transferred oocytes and descendant blastomeres of corresponding cloned embryos (Opiela et al, 2017; Monika & Selokar, 2018; Samiec & Skrzyszowska, 2018 a , 2018 b ; Zhou et al, 2020); (4) molecular and epigenetic communication between nuclear and mitochondrial genomes in nuclear-transferred oocytes and resultant cloned embryos (Hiendleder et al, 2003; Samiec, 2005 a , 2005 b ; Srirattana et al, 2011); (5) the strategies applied to artificially activate embryo-specific developmental programme of nuclear-transferred oocytes (Saikhun et al, 2004; Samiec & Skrzyszowska, 2010, 2014; George et al, 2011); and (6) the frequency of occurrence of apoptosis-dependent events in the in vitro -cultured nuclear donor cells and SCNT-derived embryos (Cui et al, 2011; Samiec et al, 2013; Agrawal et al, 2018; Mehta et al, 2019; Samiec et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional memory has been confirmed during SCNT reprogramming [ 25 ], and the transcription profile of the donor cells is preserved in SCNT embryos, owing to incomplete reprogramming. Zhou et al (2020) reported that both abnormal transcriptional activation and transcriptional silencing are involved in the development of bovine SCNT embryos [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional memory has been confirmed during SCNT reprogramming [ 25 ], and the transcription profile of the donor cells is preserved in SCNT embryos, owing to incomplete reprogramming. Zhou et al (2020) reported that both abnormal transcriptional activation and transcriptional silencing are involved in the development of bovine SCNT embryos [ 25 ]. They summarized 70 abnormally active memory genes and 45 abnormally silent memory genes inherited from donor cells, which were conserved between bovine and mouse reprogramming [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations